Digital Visual Grammar Concept Map Facilitated EFL Holistic Grammar Comprehension - Jonathan Y. Chin; Ben Chang; Yen-An Shih (Pascasarjana Universitas Negeri Makassar, 2023)
Form-focused deductive grammar learning approach is an effective way to facilitate language learners to memorize atomistic grammatical rules. However, beyond retaining isolated grammar rules, learners can benefit from using web based concept map, a visualized utility, to overlap grammar rules and achieve holistic comprehension. Therefore, this research looks into detail (total nodes, depth, and breadth) of how visual grammar concept map affects studentâ€™s examination score and aims to assist students to gain a holistic visual grammar learning through utilizing an online concept map software (CoCoing.info). One hundred and thirty-two college students were involved in this study for 18 weeks. The quantitative results revealed that students who created a more developed and holistic visual grammar concept map gained a better understanding of the grammatical rules. This was however not true for low achieving students. Therefore, more detailed analysis showed students with deeper depth and wider breadth achieved higher score. However, the high achieving students and low achieving studentsâ€™ comparison study indicated that the depth of the visual grammar concept map is harder for students to construct and is a better indicator of achievement compared to breadth. The findings show that visual grammar concept map can facilitate traditional form-focused classroom.Â